Persepsi Pengguna Tiktok Shop Terhadap Regulasi Pemerintah Menutup Aktivitas Jual Beli - Elvira Ayu Lestari; Agnita Yolanda (Mahesa Research Center, 2025)
This study aims to analyze TikTok Shop users' perception of government regulations that close direct buying and selling activities on the application on October 4, 2023. Using a descriptive quantitative approach, data was collected through an online questionnaire distributed to 89 active students of FISIP University of Medan Area, who are TikTok Shop users. Data analysis was carried out using validity, reliability, and simple linear regression tests to measure the relationship between user perception and government regulations. The results of the study show that the majority of respondents (66%) do not agree with this regulation, considering it as a restriction on access to affordable goods, especially for Generation Z who are used to shopping at TikTok Shop. This negative perception is influenced by convenient shopping experiences and economic factors, although a small percentage of respondents see these regulations as a positive step to protect consumers and create healthy competition. These findings underscore the importance of transparent communication between the government and the public to improve perceptions of the policy, as well as reduce uncertainty and socio-economic impacts.